2001
DOI: 10.1038/sj.onc.1204632
|View full text |Cite
|
Sign up to set email alerts
|

The ERK-dependent signalling is stage-specifically modulated by FSH, during primary Sertoli cell maturation

Abstract: Primary cultures of Sertoli cells provide an interesting model to study how signalling pathways induced by a single hormone in a single cell type evolve, depending on the developmental stage. In vivo, follicle-stimulating hormone (FSH) induces proliferation of Sertoli cells in neonate and controls the subsequent di erentiation of the entire population. Molecular mechanisms underlying Sertoli cell pleiotropic responses to FSH have long been investigated. But to date, only cAMP-dependent kinase (PKA) activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(157 citation statements)
references
References 49 publications
8
147
1
1
Order By: Relevance
“…However, the direct activation of B-Raf by Rap1 is still doubtful, leaving the question of how B-Raf is activated downstream from neural growth factor and cAMP in PC12 cells. It has been suggested that Src is needed for ERK activation by cAMP/PKA in B-Raf-positive cells (20,41,42). Src inhibition with PP1 does not affect uveal melanoma cell proliferation, thus ruling out a role of Src for mediating PKA-induced ERK1/2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the direct activation of B-Raf by Rap1 is still doubtful, leaving the question of how B-Raf is activated downstream from neural growth factor and cAMP in PC12 cells. It has been suggested that Src is needed for ERK activation by cAMP/PKA in B-Raf-positive cells (20,41,42). Src inhibition with PP1 does not affect uveal melanoma cell proliferation, thus ruling out a role of Src for mediating PKA-induced ERK1/2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, FSH mainly signals via cAMP-dependent PKA activation, although it also activates the MEK/ERK cascade. This occurs either in parallel via a differentially spliced receptor (18) or downstream of cAMP (20). MEK/ERK-dependent FSH effects are readily abrogated by the specific MEK inhibitor PD98059 in porcine granulosa cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, FSH does not act solely via cAMP, since it also stimulates mitogen-activated protein kinase pathways via an alternatively spliced FSH receptor in porcine granulosa cells (18). Furthermore, FSH can activate mitogen-activated protein kinase pathways downstream of PKA in mammalian granulosa cells (19) as well as Sertoli cells (20,21). There is increasing evidence suggesting that activins are not only endocrine regulators of FSH availability but also potent effectors of autocrine or paracrine intraovarian signaling.…”
mentioning
confidence: 99%
“…On this note, we anticipated that endogenous protein-tyrosine phosphatase inhibitors could protect samples from unwanted activities of proteintyrosine phosphatase; however, a complete blockade of protein-tyrosine phosphatase could shift the base line of the intrinsic kinase activity, but plausibly not the trend of activation. Furthermore, EGF (a well known receptor protein-tyrosine kinase), which was present in the Sertoli cell cultures at 2.5 ng/ml as a growth factor in our experiments as described previously (44,45), has recently been shown to stimulate Sertoli cell ERK activity at 100 ng/ml (46,47). As such, additional controls were included in Sertoli-germ cell co-cultures in which EGF was omitted in the nutrient mixture F-12/DMEM.…”
Section: Methodsmentioning
confidence: 99%